A SPATIAL APPROACH TO THE MANAGEMENT OF THE ECONOMIC POTENTIAL OF THE ENTERPRISE IN THE CONDITIONS OF NEO-TECHNOLOGICAL UPDATE - TULCHYNSKA, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The study is devoted to substantiating the principles of managing the economic potential of manufacturing enterprises in the conditions of neo-technological renewal using a spatial approach. The article substantiates that neo-technological renewal involves the intensification of the process of economic reproduction, which is achieved by fundamentally changing production processes due to the differentiation of labor, the transformation of scientific and technological potential into production power, creative approaches and rationalization of production. In the study, the economic potential of the production enterprise is considered as a certain system that has all the properties inherent in the system, which consists of a set of component subsystems whose effectiveness is greater than the effectiveness of their individual parts, and also has a unique structure for each enterprise, which ensures the development of the enterprise and the opportunity increasing competitiveness in the conditions of neo-technological renewal. It is substantiated that the economic potential of a manufacturing enterprise in the conditions of neotechnological renewal is determined by its real and latent opportunities in a certain sphere of economic activity, taking into account spatial features. It is noted that the management of the economic potential of the enterprise is a complex, continuous process aimed at achieving the set goals, through a flow of interrelated actions, that is, management functions related to the adoption of management decisions, various communication processes, the selection of tools for achieving the set goals, etc. It is proved that the spatial approach to the management of the economic potential of a manufacturing enterprise in the conditions of neo-technological renewal makes it possible: first, to clearly establish and structure a hierarchy of intermediate goals regarding the use of the economic potential of the enterprise for the purpose of its neo-technological renewal; secondly, to achieve interoperability of management functions with the use of latent capabilities due to a certain space of a component of a production enterprise; thirdly, flexibility to adapt to the performance of assigned tasks; fourth, to increase the set of economic potential management tools, which is determined by the nature of the identified goals of using the economic potential of the enterprise.